Language Editors: Challenges, Linguistic Attitudes and Motivation - Micutaitė, Neringa; Jakaitė-Bulbukienė, Kristina (Lietuvių kalba, 2023)
The aim of this work is to analyse the challenges that language editors face when editing texts and to investigate the linguistic attitudes and motivation of editors. The paper analyses 10 qualitative in-depth semi-structured interviews with language editors. The average length of each interview is 45 minutes. The research material consists of a total of 7 hours of audio recordings of the interviews, the transcribed recordings make up 100 pages of text. The texts edited by the participants vary in their nature: cultural, legal, film texts, scientific, medical, culinary, business, fiction literature and etc. It has been found that language editors face various challenges in their work: for example, difficulties due to late Lithuanian terminology, liberalising Lithuanian language policy. The linguistic attitudes of the editors have been analysed: the participants in the study do not question the idea of language normalization and explain its importance with various arguments. They stress the prestige of the common language and the difference between public and private language. The participants of the study criticise some aspects of the Lithuanian language policy: some decisions of The State Commission of the Lithuanian Language are questioned, as well as language purism. The most important aspect of language editing, according to the editors, is the fluency and clarity of the text. It was found that most of the informants feel that they contribute to the development of the language and influence the language.
Keywords: language editors; editing; linguistic attitudes; language policy; standard language